WORKSHOP PENINGKATAN KEMAMPUAN PEMBUATAN DETERGEN CAIR SEBAGAI UPAYA MENGAKTIFKAN PENGURUS PKK DESA FAJAR BARU - Agung Abadi Kiswandono; Nurhasanah Nurhasanah; Jamiatul Akmal (Politeknik Negeri Sriwijaya, 2020)
Fajar Baru Village was originally an Karang Anyar Village, Tanjung Bintang District. The vision of this village is to Build Community Together Towards Independence. This vision is realized in the form of a mission that is with the community to realize Fajar Baru Village that is prosperous, healthy and independent. One form of prosperity and independence contained in the Medium-Term Development Plan (RPJM) of Fajar Baru Village is the growth and development of several business activity groups framed in Home Industry (home industry) activities. The manufacture of household cleaning products, such as detergents, is one of the products that has the potential to become a Home Industry activity. Based on the results of a survey by the Implementation Team, the work program of the PKK Fajar Baru village group, especially the making of liquid soap, even though it was carried out, was only limited to making and producing for themselves (the management itself). The results show that, the knowledge of the PKK Fajar Baru Village mothers about